2001
DOI: 10.1126/science.1064126
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Therapy with Targeted Atomic Nanogenerators

Abstract: A single, high linear energy transfer alpha particle can kill a target cell. We have developed methods to target molecular-sized generators of alpha-emitting isotope cascades to the inside of cancer cells using actinium-225 coupled to internalizing monoclonal antibodies. In vitro, these constructs specifically killed leukemia, lymphoma, breast, ovarian, neuroblastoma, and prostate cancer cells at becquerel (picocurie) levels. Injection of single doses of the constructs at kilobecquerel (nanocurie) levels into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
406
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(421 citation statements)
references
References 11 publications
6
406
0
2
Order By: Relevance
“…This latter isotope is an in vivo isotope generator, in that it has a long (10 day) half-life and decays via alpha emission through 3 shortlived atoms, each of which yields an alpha particle (12,14). Previous work in our laboratory led to the synthesis, purification and analysis of 225 Ac stably bound to the IgG via a bifunctional macrocyclic chelator DOTA (1,4,7,10-tetraazacyclodoecane-1,4,7,10-tetraacetic acid) (15). These constructs specifically killed leukemia and cancer cells at becquerel (picocurie) levels in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter isotope is an in vivo isotope generator, in that it has a long (10 day) half-life and decays via alpha emission through 3 shortlived atoms, each of which yields an alpha particle (12,14). Previous work in our laboratory led to the synthesis, purification and analysis of 225 Ac stably bound to the IgG via a bifunctional macrocyclic chelator DOTA (1,4,7,10-tetraazacyclodoecane-1,4,7,10-tetraacetic acid) (15). These constructs specifically killed leukemia and cancer cells at becquerel (picocurie) levels in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…These short ranged particles may be capable of single cell kill while sparing bystanders. High LET alpha emitters used in radioimmunotherapy include Bismuth-212 (10)(11)(12) and -213 (13)(14)(15), Astatine-211 (16), and Actinium-225. This latter isotope is an in vivo isotope generator, in that it has a long (10 day) half-life and decays via alpha emission through 3 shortlived atoms, each of which yields an alpha particle (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Other antibodies to PSMA are reported to react with the membrane-proximal region of the extracellular domain. 28,29 Although several of these are being developed as therapeutic recombinants, e.g., for targeted delivery of radioisotopes 31 or as PSMA/CD89 diabodies for attracting effector cells to prostate tumors, 32 at present PSMA MAbs do not appear to have direct antibody-mediated tumor cytotoxicity. Although the tumoricidal activities of trastuzumab and C225 are readily explainable through blocking vital surface receptors, the role of PSMA in prostate tumor survival is not understood at present.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology is also enabling highly efficent radiotherapy, such as the injection of single doses of an atomic nanogenerator at kilobecquerel (nanocurie) levels into mice bearing solid prostate carcinoma or disseminated human lymphoma induced tumour regression and prolonged survival, without toxicity, in a substantial fraction of animals (McDevitt et al, 2001). In another study, metal nanoshells with tunable optical resonance were shown to induce irreversible thermal damage to tumour cells when exposed to near infrared light (Hirsch et al, 2003).…”
Section: Future Directionsmentioning
confidence: 99%